Anti-inflammatory iridoid glycosides from fruits of Cornus officinalis. (December 2022) - Wang, Xin; Wu, Yong; Wang, Ze-yu; Li, Jin-jie; Li, Wen; Li, Qian; Luan, Na; Shang, Xiao-ya
Abstract: Three undescribed iridoid glycosides, cyc(7 β - O -6′)-morroniside (1 ), 6′-methyl succinate-7 β - O -methylmorroniside (2 ), and 7 β - O -methyl phenyllactate morroniside (3 ) were isolated from 50% ethanol extract of Cornus officinalis fruits. The structures of the isolated compounds were determined by HRESIMS, 1 D NMR, 2 D NMR, UV and IR spectroscopic methods. Compounds 1 -3 exhibited moderate anti-inflammatory activities in vivo in a CuSO4 -induced zebrafish inflammation model (when evaluated at 50 μM). Graphical Abstract: ga1 Highlights: Three undescribed iridoid glycosides were isolated from Cornus officinalis fruits. The structures were established by spectroscopic data. All compounds showed anti-inflammatory activity on zebrafish inflammation model.